Changes in intravascular complement, kininogen, and histamine during Jarisch-Herxheimer reaction in secondary syphilis. Issue 1 (February 1985) - Loveday, C; Bingham, J S
Abstract : Nine patients with secondary syphilis and one control subject were observed for eight hours after the administration of penicillin. Serial clinical observations were made, and blood samples were obtained for the analysis of complement, histamine, and kininogen. Six patients showed Jarisch-Herxheimer reactions, the intensities of which were found to parallel certain changes in activity of complement and concentrations of histamine and kininogen. Results were analysed statistically. Significant falls were seen in: total haemolytic complement (CH50), C1 inhibitor, C3, functional (haemolytic) C4, and to a lesser extent total C4. Split products of C3 were shown in five of the six patients who had a reaction. There was no change in total glycine rich beta-glycoprotein (GBG) or glycine rich gamma-glycoprotein (GGG) or evidence of conversion of GBG to GGG. Plasma kininogen concentrations fell and plasma histamine concentrations rose appreciably before and during the clinical phase of the reaction. These results are discussed in relation to the clinical features and possible pathogenic mechanisms of the Jarisch-Herxheimer reaction.